Effects of airflow rates and operator activity on containment of bacterial aerosols in a class II safety cabinet. - Macher, J M (1984)
Biological safety cabinets are frequently relied upon to provide sterile work environments in which hazardous microorganisms can be safely handled. Verification of correct airstream velocities does not, by itself, ensure that adequate protection will be achieved under all users. Instead, the concentration of microorganisms in a cabinet operator's breathing zone must be measured during typical cabinet use conditions to determine whether the exposure is below acceptable limits. In this study, cabinet operator exposures were measured with a personal air sampler. Bacterial spores were released inside a cabinet as a uniform challenge aerosol, and the number of escaping spores was measured for several cabinet arrangements during a number of typical operations. The following were studied to determine their effects on aerosol containment: inflow air velocity, size of access opening, type of operator movements, location of operator's hands, and pace of activity. Other experiments examined differences in aerosol containment for eight typical microbiology operations when performed by six operators who covered a range of body heights and volumes.